2015
DOI: 10.1007/s10396-015-0688-3
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of transthoracic left atrial appendage wall velocity measurement in addition to left atrial volume for noninvasive and quantitative assessment of left atrial thrombogenesis in patients with atrial fibrillation and normal D-dimer levels

Abstract: The noninvasive measurement of transthoracic LAAWV in addition to LA volume is clinically relevant for quantitatively assessing thrombogenesis in AF patients with normal D-dimer levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Twelve (57.1%) studies confined the population to patients with AF [ 13 , 19 , 20 , 21 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ], with reported percentages of patients with AF ranged from 20%-86% in 7 (33.3%) studies [ 12 , 18 , 22 , 32 , 33 , 34 , 35 ], besides, 2 (9.5%) studies focused on patients in sinus rhythm [ 23 , 36 ], 4 studies (19.0%) restricted to the population of patients with mitral stenosis [ 23 , 33 , 35 , 36 ], among which, 2 studies reported the prevalence of mitral stenosis ranged from 6.0% to 27.5% [ 28 , 37 ]. Of 21 included studies, 12 (57.1%) studies reported mean or median DD values [ 13 , 18 , 19 , 24 , 25 , 26 , 27 , 29 , 30 , 32 , 35 , 37 ], 5 (23.8%) studies reported frequency and DD cutoff value on LAT [ 22 , 23 , 31 , 33 , 34 ], and 4 (19.0%) studies reported both [ 12 , 20 , 21 , 36 ]. 11 studies have available information to calculate a ratio of the presence of LAT among individuals in the top vs bottom third of DD levels[ ...…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Twelve (57.1%) studies confined the population to patients with AF [ 13 , 19 , 20 , 21 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ], with reported percentages of patients with AF ranged from 20%-86% in 7 (33.3%) studies [ 12 , 18 , 22 , 32 , 33 , 34 , 35 ], besides, 2 (9.5%) studies focused on patients in sinus rhythm [ 23 , 36 ], 4 studies (19.0%) restricted to the population of patients with mitral stenosis [ 23 , 33 , 35 , 36 ], among which, 2 studies reported the prevalence of mitral stenosis ranged from 6.0% to 27.5% [ 28 , 37 ]. Of 21 included studies, 12 (57.1%) studies reported mean or median DD values [ 13 , 18 , 19 , 24 , 25 , 26 , 27 , 29 , 30 , 32 , 35 , 37 ], 5 (23.8%) studies reported frequency and DD cutoff value on LAT [ 22 , 23 , 31 , 33 , 34 ], and 4 (19.0%) studies reported both [ 12 , 20 , 21 , 36 ]. 11 studies have available information to calculate a ratio of the presence of LAT among individuals in the top vs bottom third of DD levels[ ...…”
Section: Resultsmentioning
confidence: 99%
“…Of 21 included studies, 12 (57.1%) studies reported mean or median DD values [ 13 , 18 , 19 , 24 , 25 , 26 , 27 , 29 , 30 , 32 , 35 , 37 ], 5 (23.8%) studies reported frequency and DD cutoff value on LAT [ 22 , 23 , 31 , 33 , 34 ], and 4 (19.0%) studies reported both [ 12 , 20 , 21 , 36 ]. 11 studies have available information to calculate a ratio of the presence of LAT among individuals in the top vs bottom third of DD levels[ 20 , 21 , 22 , 23 , 24 , 28 , 29 , 31 , 33 , 34 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations